2019
DOI: 10.1001/jamainternmed.2018.8351
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Study Time Reduction Using Surrogate End Points Rather Than Overall Survival in Oncology Clinical Trials

Abstract: IMPORTANCE Surrogate end points in oncology trade the advantage of reducing the time needed to conduct clinical trials for the disadvantage of greater uncertainty regarding the treatment effect on patient-centered end points, such as overall survival (OS) and quality of life. OBJECTIVE To quantify the amount of time saved through the acceptance of surrogate end points, including response rate (RR) and progression-free survival (PFS). DESIGN, SETTING, AND PARTICIPANTS This retrospective study of US Food and Dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 17 publications
1
86
0
Order By: Relevance
“…The use of surrogate endpoints such as response rate and progression-free survival has been associated with a reduction in oncologic clinical trial reporting times [15]. Echoing these findings, our results demonstrate an association between surrogate endpoint use and reduced TTR on univariate analysis, although this association was not observed on multivariate analysis.…”
Section: Discussionsupporting
confidence: 68%
“…The use of surrogate endpoints such as response rate and progression-free survival has been associated with a reduction in oncologic clinical trial reporting times [15]. Echoing these findings, our results demonstrate an association between surrogate endpoint use and reduced TTR on univariate analysis, although this association was not observed on multivariate analysis.…”
Section: Discussionsupporting
confidence: 68%
“…Surrogate measures of clinical benefit (eg, progression free survival and disease response) have important feasibility advantages because they can be assessed earlier and with smaller sample sizes (and therefore fewer resources) compared with overall survival. A recent study found that cancer drugs approved on the basis of surrogate measures had on average an 11 month shorter development duration compared with drugs approved on the basis of overall survival 81. However, the feasibility advantages of using surrogate measures should be weighed against their several disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent evaluation, using progression-free survival and response rate in cancer trials was associated with an average 11-month and 19month, respectively, shorter clinical development period compared with using overall survival. 62 Although certain surrogate measures are well-validated, many of the surrogate measures used for approval decisions are not comprehensively validated, highlighting the need to confirm clinical benefit in the post-marketing period. Surrogate measures are particularly common in cancer trials.…”
Section: Choice Of Study Outcomesmentioning
confidence: 99%